Urban agriculture as an innovative production constitutes an element that integrates and complements the city’s structure - Grochulska-Salak, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Urban agriculture is defi ned as development for the production of plants for the needs of the local community. The presented problems concern the shaping of buildings together with the green systems in order to preserve the environmental balance of urban spaces and the connections between the coexistence of architecture and greenery in the city. It is pointed out the possibility of shaping synergistic spatial arrangements by integrating urban space and development with an innovative production function – urban farm – complementing the functional structure of the city in connection with the shaping of public spaces and the green system. Pro-environmental architecture is linked to technologies that enable plant production in buildings to integrate urban space, complementing the city’s functional-spatial structure. The implementation of new technologies enables the production of plants in hydroponic and aerospace buildings. The technology of production and the program and structure of urban farm buildings are the subject of research and analysis, in order to shape integrated urban space development in the context of the urban unit’s autarky. It is pointed out the need to increase the scope of production of material and non-material goods realized in the team of urban farm. Linking with public spaces and realization of public utility buildings is justified by shaping the land development and development program for the needs of the local community. Urban agriculture can be an element that integrates the city’s structure. It should be implemented in nodal areas in connection with the systems of: road communication, public spaces and urban greenery.